Simple Rules for a Complex World - Epstein, Richard Allen (Harvard University Press, 2022)
Too many laws, too many lawyers--that's the necessary consequence of a complex society, or so conventional wisdom has it. Countless pundits insist that any call for legal simplification smacks of nostalgia, sentimentality, or naiveté. But the conventional view, the noted legal scholar Richard Epstein tells us, has it exactly backward. The richer texture of modern society allows for more individual freedom and choice. And it allows us to organize a comprehensive legal order capable of meeting the technological and social challenges of today on the basis of just six core principles. In this book, Epstein demonstrates how. The first four rules, which regulate human interactions in ordinary social life, concern the autonomy of the individual, property, contract, and tort. Taken together these rules establish and protect consistent entitlements over all resources, both human and natural.